Intravenous Pantoprazole: A New Tool for Acutely Ill Patients Who Require Acid Suppression - Eric F Trépanier (Canadian Journal of Gastroenterology)
Until now, oral proton pump inhibitors have not been available as parenteral therapy in the acute care setting. Pantoprazole is the first parenteral proton pump inhibitor to become available in Canada. This agent is superior to the parenteral histamine2 receptor antagonists with respect to acid suppressive effects and is not associated with tolerance development. Another advantage over the histamine2 receptor antagonists is that pantoprazole does not require dosage adjustment in patients with renal impairment. Dosage adjustments are also not required for elderly patients or those with hepatic impairment when the drug is used at the usual dose for a limited period of time. Contrary to intravenous cimetidine and ranitidine, which have negative inotropic and chronotropic effects, intravenous pantoprazole is well tolerated and has no significant effect on heart rate, contractility or blood pressure. The lack of drug interactions for this agent also simplifies its use, especially in patients who may require multiple drugs during hospitalization. Parenteral pantoprazole is effective in the treatment of reflux esophagitis. It is also promising for the treatment of upper gastrointestinal bleeding and in the perioperative care of patients with Zollinger-Ellison syndrome, but further research in these areas is necessary. Once the patient is able to tolerate oral medications, parenteral therapy can be easily converted to oral therapy using an oral dose that was equivalent to the parenteral dose (ie, 40 mg given intravenously is equivalent to 40 mg given orally).